Analisis Pengendalian Internal Pada Proses Pembukaan Rekening Nasabah di PT Bank Sumsel Babel Syariah Capem Muhammadiyah Palembang - Nur Wulan Septiani; Mega Silvia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the implementation of the internal control system in the customer account opening process at PT Bank Sumsel Babel Syariah CAPEM Muhammadiyah Palembang and to evaluate its compliance with applicable procedures and regulations. Adequate internal control is crucial for Islamic banking to mitigate operational risks, ensure customer data security, and maintain compliance with Sharia principles. The research method used is descriptive qualitative with a case study approach. Data were collected through direct observation during the internship, interviews, and documentation of bank operational procedures. The results show that PT Bank Sumsel Babel Syariah CAPEM Muhammadiyah Palembang has implemented internal control elements based on the COSO framework, such as the control environment, risk assessment, control activities, information and communication, and monitoring. Although procedures are in place, operational obstacles were still identified, such as incomplete customer requirement documents and data entry errors. This study concludes that although the internal control system has been implemented, strengthening is needed in document verification aspects and continuous supervision to minimize the risk of administrative errors and improve service effectiveness.